Genetic diversity of pepper (Capsicum spp.) germplasm resources in China reflects selection for cultivar types and spatial distribution - Xiao-min ZHANG; Zheng-hai ZHANG; Xiao-zhen GU; Sheng-li MAO; Xi-xiang LI; Joël Chadœuf; Alain Palloix; Li-hao WANG; Bao-xi ZHANG (Journal of Integrative Agriculture, 2016)
Pepper (Capsicum spp.) is an important vegetable crop in the world. Now the pepper in China contributes one-third of the world's peppers production. Genetic diversity of the pepper germplasm of China is expected interesting to know. To explore the structure of genetic diversity in Chinese pepper germplasm resources and possible relationship with cultivar types or geographic origin, we sampled and compared 372 GenBank pepper accessions (local cultivars and landraces) from 31 provinces, autonomous regions and municipalities of China and 31 additional accessions from other countries. These accessions were genotyped using 28 simple sequence repeat (SSR) markers spanning the entire pepper genome. We then investigated the genetic structure of the sampled collection using model-based analysis in STRUCTURE v2.3.4 and examined genetic relationships by the unweighted pair-group method of mathematical averages (UPGMA) in MEGA. In addition to geographic origin, we evaluated eight plant and fruit traits. In total, 363 alleles were amplified using the 28 SSR primers. Gene diversity, polymorphism information content and heterozygosity of the 28 SSR loci were estimated as 0.09–0.92, 0.08–0.92 and 0.01–0.34, respectively. The UPGMA cluster analysis clearly distinguished Capsicum annuum L. from other cultivated pepper species. Population structure analysis of the 368 C. annuum accessions uncovered three genetic groups which also corresponded to distinct cultivar types with respect to the plant and fruit descriptors. The genetic structure was also related to the geographic origin of the landraces. Overall results indicate that genetic diversity of Chinese pepper landraces were structured by migration of genotypes followed by human selection for cultivar types in agreement with consumption modes and adaptation to the highly diversified agro-climatic conditions.